(untitled) (Third Sector Social Economic Review, 2022)
This research was created to examine how the child-rearing attitudes of the administrative staff at the university differ according to various variables. In the study, a screening model was used to determine child-rearing attitudes. It is a descriptive research aiming to investigate the situation. The sample of the research consists of 203 administrative staff working at Giresun University in the 2020-2021 academic year. Personal Information Form and Family Life and Child Rearing Attitude Scale (PARI) were used to collect data in the study. According to the results of the study, a statistically significant difference was found in the child-rearing attitudes of the university personnel according to some variables. These variables are gender, age, education level, staff title, marital status, family type, living in a relative at home and marriage type. According to the findings obtained from the study, women have higher ""husband-wife discord"" attitudes compared to men. Men mostly adopt ""overprotective"" and ""pressure-discipline"" attitudes. It was concluded that the attitudes of ""refusal to be a housewife"", marital discord, and ""pressure-discipline"" of young personnel are higher than other personnel. In addition, it was observed that the ""overprotective"" and ""pressure-discipline"" attitudes of the personnel with low education level were higher.As a result of the comparison according to marital status, it was concluded that the attitudes of ""husband-wife incompatibility"" and ""rejection of housewifery"" of single personnel are higher than those of married personnel.